Leveraging H2 reduction, hydrometallurgy and chlor-alkali electrolysis for recycling waste LiCoO2 electrode of spent Li-ion batteries - Zhou, Jiayin; Liu, Jingdian; Yang, Shaoyu; Xu, Chao; Guan, Xiaofei (Sustainability & Circularity NOW)
The recycling of Li-ion batteries not only reduces dependence on primary mineral resources but also mitigates environmental contamination associated with improper disposal. To advance the development of Li-ion battery recycling technologies, this study presents an integrative process for the recovery of waste LiCoO2 by harnessing the advantages of H2 reduction, hydrometallurgy, and chlor-alkali electrolysis. The waste LiCoO2 was first treated with H2 reduction roasting at 400 ºC. The roasted product was then subjected to water leaching, achieving a Li leaching efficiency of ~96% within merely 5 minutes under 26 ºC and a solid-to-liquid ratio of 1/14 g/mL, and resulting in a solid mixture of LiOH and Li2CO3 after evaporation and drying. Subsequently, the solid residue insoluble in the previous step of water leaching was subjected to HCl leaching and then NaOH precipitation to recover Co in the form of Co(OH)2. Both HCl and NaOH utilized can be derived from chlor-alkali electrolysis. Finally, the Co(OH)2 and the mixture of LiOH and Li2CO3 recovered were used as raw materials to synthesize new LiCoO2. Overall, this entire process enables a closed loop, increases the utilization efficiency of HCl to near unity, and can in principle avoid the production of liquid or solid wastes.